Diagnostic, clinical and epidemiological aspects of dairy cows naturally infected by trypanosoma vivax in the states of pernambuco and alagoas, Brazil - De Andrade Neto, Adony Querubino; De Mendonça, Carla Lopes; Souto, Rodolfo José Cavalcanti; Sampaio, Paulo Henrique [UNESP]; Fidelis, Otávio Luiz [UNESP]; André, Marcos Rogério [UNESP]; MacHado, Rosangela Zacarias [UNESP]; Afonso, Jose Augusto Bastos (Revista Brasileira de Medicina Veterinaria, 2019)
Trypanosoma vivax is the most pathogenic hemoparasite of ruminants, causing huge economic losses to the producer when prevalent in the herd. This study aims to characterize the trypanosomiasis in naturally infected cattle in order to assess the clinical findings, epidemiological risk factors, and diagnosis of this disease in outbreaks occurring in the states of Pernambuco and Alagoas, northeastern Brazil. For this purpose, historical and clinical examinations, blood collection and clinical monitoring were performed in 109 animals presenting illness for a period of one year. The main clinical findings were fever, apathy, anorexia, diarrhea, progressive weight loss, lymphadenopathy, pale mucous, incoordination, aggressiveness, abortion, decrease in milk production, and high mortality. Out of 109animals, 94% (103/109) were seropositive to Trypanosoma vivax by ELISA, 92% (100/109) were seropositive for IFAT, 15% (17/109) were positive in conventional PCR assay based on the cathepsine L gene, and 9% (10/109) showed the presence of Trypanosoma vivax trypomastigotes in stained-blood smears. In 13 samples, blood counts revealed that 69.23% (9/13) showed normocytic normochromic anemia and 53.84% (7/13) had leukocytosis, in 46.15% (6/13) neutrophilia and regenerative left shift. In 72 samples, the hematocrit, plasma protein, and fibrinogen were also examines. The hematocrit presented an average of 22% (10% to 37%), plasma protein a mean value of 7.55 g/dl (5.4 g/dl to 10.0 g/dl), and plasma fibrinogen a mean value of 700mg/dl (200mg/dl to 1600mg/dl). The sequencing of DNA samples revealed 100% identicalness to Trypanosoma vivax by BLAST analysis. The main factors involved in the spread of the disease were: the ingress of animals without prior tests and quarantine into the properties, application of oxytocin with shared needles contaminated by blood at the time of lactation, and the restriction of the disease in the lactation herd. The transmission of Trypanosoma vivax occurred through the sharing of needles among lactating animals during application of oxytocin after the entry of carrier animals in the herd. Serological tests demonstrated a high rate of seropositive animals, however, conventional PCR and blood smears revealed a low positive rate because the animals were already being treated with trypanocid drugs. It is concluded that trypanosomiasis is a disease to be considered in the cattle regions studied as the cause of outbreaks. Hygiene and security actions should be taken during the administration of oxytocin in lactating cows. In fact, this practice, when performed using shared needles and without disinfection, is the main risk factor in the transmission of trypanosomiasis in dairy herds among regions where the disease is prevalent, increasing the challenge of reinfection of animals. Copyright Andrade Neto et al.
Keywords: Diagnosis; Ruminant; Trypanosoma vivax